THE EFFECT OF BRAND CREDIBILITY AND BRAND PRESTIGE ON RELATIONSHIP QUALITY: THE PERSPECTIVE OF YOUNG CONSUMERS IN THE PREMIUM CINEMA - Aditya Pandowo (AIBPM Publisher, 2018)
The purpose of this paper is to investigate the role of brand credibility and brand prestige as antecedents of brand attachment and their effect to brand love. 160 respondents are eligible in survey method collected by purposive sampling, which is young premium cinema audiences is the criteria. The instruments measurement through validity and reliability were running before the hypotheses testing. The study found that brand credibility affect brand attachment and brand love directly. Though brand prestige predicts brand love significantly, but failed to perform the same role to brand attachment. Our study contributes to enhance managers to provide credible brand to catch young hedonic customers and suggests them to be attached and maintain relationship with customers in order to build brand love. Keywords: brand credibility, brand prestige, brand attachment, brand love.